Шляхетські замки XIV–XVIII ст. у верхів’ях р. Стир: питання реєстру - Каша, М. Є. (Видавництво Львівської політехніки, 2013)
Розглянуто історико-археологічну характеристику шляхетських замків у верхів’ях р. Стир. Проаналізовано еволюцію поглядів істориків на формування мережі шляхетських замків, а також результати археологічних розвідок та розкопок протягом XIX–XX ст. Констатовано недостатню увагу щодо збереження та вивчення пам’яток цього типу. Historical and archaeological description of noble castles in the riverheads of the Styr has been considered in the article. The evolution of historians’ views concerning the formation of the network of noble castles and also the results of archaeological surveys and excavations during XIX–XX century have been analyzed. It has been found out that insufficient attention is paid to preservation and study of such monuments.